PENGARUH UKURAN PERUSAHAAN, KONEKSI POLITIK DAN STRUKTUR KEPEMILIKAN INSTITUSIONAL TERHADAP TINGKAT AGRESIVITAS PAJAK - Alviana Yunita Layli; Adi Sofyana Latif (Jurnal Nusa Akuntansi, 2026)
This study aims to examine and prove the influence of company size, political connections, and institutional ownership structure on the level of tax aggressiveness in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. This study uses a quantitative approach with secondary data obtained from annual reports and company financial reports. The research sample was selected using a purposive sampling technique, with a total of 70 observations. The analytical method used is multiple linear regression analysis, and data processing was carried out using E-Views 13 software. The results of the study indicate that partially, the company size variable has no effect on tax aggressiveness, political connections affect tax aggressiveness, and institutional ownership structure affects tax aggressiveness. These findings imply that political connections and ownership structure play an important role in corporate tax management practices. The results of the study simultaneously show that company size, political connections, and institutional ownership structure together influence tax aggressiveness.